Odpowiedzi

2009-11-05T15:03:15+01:00
A)(2x²-x)(2x²+11x-6)≤0
4x⁴+22x³-12x²-2x³-11x²+6x≤0
4x⁴+20x³-23x²+6x≤0
4x³(x+5)-x(23x-6)≤0
(4x³-x)(x+5)(23x-6)≤0

4x³-x≤0
4x(x²)-x≤0

lub
x+5≤0
x≤-5

lub
23x-6≤0
23x≤6/23
x≤6/23




b)4x³+3x-8x-6>0
x(4x²+3)-2(4x+3)>0
(x-2)(4x²+3)(4x+3)>0

x-2>0
x>2

lub
4x²+3>0
4x²>-3/4
x²>-3/4
x>√-3/4
nierówność sprzeczna

lub
4x+3>0
4x>-3/4
x>-3/4


c)-3x⁴+10x³+25x²<0
-3x⁴+5x²(2x+5)<0
x²(-3x²+5)(2x+5)<0

x²<0
x<0

lub
-3x²+5<0
-3x²<-5/(-3)
x²>5/3
x>√5/3


Nie jestem pewna, czy jest dobrze.